Application of the Mechanism Design to Develop the RGB LEDs Color Mixing - Chih-Ching Hung; Yan-Huei Li; Ping-Han Yang (International Journal of Photoenergy)
The big advantage of LED is the flexible spectral design to make white light using different color mixing schemes. Recently, the color mixing of RGB LEDs is mostly done by sealing all three chips at single package and regulated the mix ratio of these three colors to produce the color of light. And, by changing the LEDs array alignment, RGB chips can achieve overlapping colors of light and create the fun of changing colors in light mixing. Therefore, the purpose of this study is to propose an innovative technique of light mixing. By applying the mechanism design, a RGB light mixing mechanism is produced. Each of the RGB LEDs lamp-type is installed on the couple link of the three mechanisms, respectively. By driving a crank makes the couple link and an output link to produce the relative motion, this will result in the fact that the RGB lamps can project lights on the same plane in order to obtain the color mixing. Unlike mixing technique by control system, this design generates light mixing and changes of color with the synchronized driving of three mechanisms, thus achieving the dazzling perception of single-color lights or mixing of multiple colors for creating ambience of a space.